Novel computerised halal pharmaceuticals supply chain framework: A quality and production case study - Raja Ikram, Raja Rina; Abd Ghani, Mohd Khanapi; Hasan Basari, Abd Samad (2013)
Computerised systems are heavily used to improve manufacturing and supply chain performance. Industry and religious authorities require a standardized rule to impose halal qualifications whenever a computerised system substitutes a manual operation [15]. The current halal pharmaceuticals standards imposed by Malaysian and Indonesian enforcement authorities mainly focus on physical activities [15]. This paper shall propose a framework to manage the halal supply chain when computerised systems are being used in the pharmaceutical industry for the quality and production module. The proposed framework is the outcome of a case study of a Malaysian pharmaceutical organization which manufactures and distributes pharmaceutical products. This framework is expected to assist researchers to understand the halal pharmaceuticals supply chain especially in the requirements phase of software development lifecycle.